Building student character through contextual learning approach : Islamic education novice teachers’ experiences - Tengku Sarina Aini Tengku Kasim,; Yusmini Md Yussof,; Fadillah Mansor, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study aims to examine how contextual learning approach influences the character development of Malaysian students. It reflects on how contextual learning activities applied by Islamic Education novice teachers can build student character and personality. This is a qualitative research underpinned by a constructivist learning theory as theoretical and analytical framework. A total of 10 Islamic Education novice teachers participated in this study. Data were collected through semi -structured individual interviews and classroom observations. Thematic analysis was utilized to analyse and present the research findings. The findings offer some significant insights into how contextual learning activities applied by the participants have directly and indirectly developed student character, values, personality and behaviour. The findings of this study reveal that contextual learning contributes to the building of student character. The findings of the study also provide educators, especially novice teachers, better understanding of excellent skills, such as contextual learning, more effectively. These skills are critical in order to be able to produce a competitive new generation in the face of life demands, in line with rapid development of Information and Communication Technology (ICT). Contextual learning when incorporated into learning will expose teachers to authentic experiences in the classroom, playing their role in developing student personality and character, together with academic performance.